RANCANGAN PINTU PADA MOBIL KHUSUS PENGGUNA KURSI RODA - Putra Mahardika, Muhammad Adit; Subkhan, Subkhan; Riyanto, Ade; Yunus, Muhammad (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
Public services should be accessible to all citizens, including persons with disabilities. However, they still face various forms of discrimination, particularly in terms of physical accessibility and neutral public service policies that do not accommodate their needs. One of the major challenges is the difficulty in using public transportation, which significantly affects their mobility, employment opportunities, and social interaction. This final project aims to design a vehicle door that is accessible and user-friendly for wheelchair users, with a focus on enhancing independent mobility. The design process refers to the VDI 2222 methodology, starting from identifying user needs, developing design concepts, to evaluating the proposed solution. One of the main issues in conventional vehicle design is the door mechanism, which often fails to consider the specific needs of wheelchair users. Common problems include narrow door openings, high floor levels, and unfriendly opening-closing mechanisms. This study proposes several modifications, such as wider door openings, lower floor height, and the use of sliding or automatic doors to improve accessibility. The proposed design is expected to offer a practical and applicable solution that enhances the mobility and quality of life of people with disabilities, especially wheelchair users, in Indonesia.